Elastoplastic analysis of reinforced concrete space frames using the uniaxial and biaxial bending method - Vieira, Pedro Cláudio dos Santos; Silva, William Taylor Matias (Acta Scientiarum. Technology, 2022)
The scope of the work involves reinforced concrete frame structures with variations in structural design conception for columns with biaxial bending or uniaxial bending. The beams are designed with simple bending criteria for singly or doubly reinforced beams, or uniaxial bending. The analysis and design criteria are according to NBR 6118:2014. Structure analysis in elastoplastic regimen with the incremental analysis method is performed to detect plastic hinge formation order, collapse load factor, displacements, and rotation capacity of cross sections with the criteria established in the current building codes. The study evaluates the influence of the defined concepts on the structure´s elastoplastic behavior. The biaxial and uniaxial bending method is presented as an important formulation for obtaining the collapse load factor using the elastic stiffness matrix with modifications. The algorithms presented enable the development of research without the need for expensive commercial software licenses.